Physical Activity, Percent Body Fat, Visceral Fat, ASMI, and Blood Pressure with Obesity in Indonesian Older Women: A Cross-Sectional Study - Muhdar, Izna Nurdianty; riyadi, hadi; Ali Khomsan; Mansur Jauhari (Nutrición Clínica y Dietética Hospitalaria, 2025)
Obesity is increasingly becoming a significant public health issue worldwide, particularly among older adults. In Indonesia, the rise of obesity among older women is particularly alarming, contributing substantially to the burden of chronic illnesses. The primary risk factors for obesity include a sedentary lifestyle, and lower muscle mass, which can increase body fat, weight gain, and other associated health problems. This study investigated the factors related to body mass index (BMI) among women. A cross-sectional design was employed to analyze the prevalence of obesity, physical activity levels, percentage of body fat, visceral fat, appendicular skeletal muscle index (ASMI), and blood pressure (BP). A total of 154 older women aged 60 to 69 were selected as respondents from three sub-districts using proportional random sampling. Data were collected through physical examinations and interviews utilizing a questionnaire. The results showed the prevalence of obesity was 42.20%, with low levels of physical activity (72.70%), 42.90% have high levels of %BF, while 37.00% exhibit high levels of visceral fat, preserved ASMI (55.20%), 94.80% showing elevated SBP and 83.80% DBP. According to Chi-square test, physical activity (OR = 2.05, 95%CI = 1.00-4.22), %BF (OR = 17.66, 95%CI = 5.75-54.25), VF (OR = 75.29, 95%CI = 21.24-266.85), ASMI (OR = 0.05, 95%CI = 0.02 – 0.12), and SBP (OR = 4.96, 95%CI = 0.96 – 25.45) were significantly associated with obesity. All in all, physical activity, %BF, visceral fat, ASMI, and SBP are risk factors for obesity among women aged 60-69. Further research needs to be conducted using a larger sample size and different study designs to explore additional factors associated with obesity in older adults.